2011
DOI: 10.1126/science.1203980
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Rhizosphere Microbiome for Disease-Suppressive Bacteria

Abstract: Disease-suppressive soils are exceptional ecosystems in which crop plants suffer less from specific soil-borne pathogens than expected owing to the activities of other soil microorganisms. For most disease-suppressive soils, the microbes and mechanisms involved in pathogen control are unknown. By coupling PhyloChip-based metagenomics of the rhizosphere microbiome with culture-dependent functional analyses, we identified key bacterial taxa and genes involved in suppression of a fungal root pathogen. More than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

62
1,541
4
36

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,164 publications
(1,760 citation statements)
references
References 59 publications
(51 reference statements)
62
1,541
4
36
Order By: Relevance
“…Our results confirmed that these organisms predominate in the rhizosphere, presumably because labile organic substrates are more available than in bulk soil. In addition, Burkholderiaceae, Xanthomonadales and Actinobacteria harbor genera and species with anti-microbial activities (Mendes et al, 2011), which may enable them to operate as interference competitors in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed that these organisms predominate in the rhizosphere, presumably because labile organic substrates are more available than in bulk soil. In addition, Burkholderiaceae, Xanthomonadales and Actinobacteria harbor genera and species with anti-microbial activities (Mendes et al, 2011), which may enable them to operate as interference competitors in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The unique ecological niche shapes the structure of rhizosphere bacterial community through the interactions of plant species, the chemical nature of root exudates, soil properties, and many other factors (Savka and Farrand, 1997). While some detrimental microbes undermine plant health, mutualistic rhizosphere microbes provide plants with mineral nutrients, phytohormones, and protect the plant against phytopathogens (Mendes et al, 2011;Singh et al, 2004;Vercellino and Gómez, 2013). Thus, to understand the suite of bacterial interactions that may occur over the lifetime of a plant, it is important to know the rhizosphere bacterial community and its variation over plant growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…The plant microbiota can influence multiple plant traits such as biomass accumulation (Sugiyama et al 2013), metabolite production , drought tolerance (Lau and Lennon 2012;Rolli et al 2015), flowering time (Wagner et al 2014;PankeBuisse et al 2015;Dombrowski et al 2017) and disease resistance (Busby et al 2016;Ritpitakphong et al 2016;Mendes et al 2011;Santhanam et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First, the mixed inocula consisted of 50% of both monospecific soils, and as such only consisted of 50% of the density of soil microorganisms of both monospecific soils. Previous studies found that a reduction in volume of a soil inoculum reduces the effect of the inoculum on the plant (St-Denis et al 2017;Mendes et al 2011;Hol Fig. 2 Relationship between the difference among two monospecific inocula on plant biomass (a) and yellowness (b), and the difference between the observed and predicted effects when mixing these two inocula.…”
Section: Discussionmentioning
confidence: 99%